(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nazar IA, Sutarno, Mudofir, Sunarto. 2024. Plant biodiversity and people’s behavior on environmental conservation in Pabelan Islamic Boarding School, Magelang, Central Java, Indonesia. Biodiversitas 25: 232-239. Pabelan Islamic Boarding School is a modern educational institution committed to religious-based environmental education. The landscape of this Islamic boarding school is designed to contribute to the preservation of the surrounding environment. This study aims to determine plant diversity and behavioral patterns in environmental conservation in Pabelan Islamic Boarding School, Magelang District, Central Java, Indonesia. Vegetation analysis was conducted by inventory of tree species planted in the area of the school. Analysis of the behavior patterns was carried out using observation, interviews with the clerics (kiai), teacher (ustaz) and staff, and questionnaires to students. The result of vegetation analysis showed that Pabelan Islamic boarding school has a moderate level of flora diversity with a Shannon-Wiener index (H’: 2.597). This is because the management of the school has a unique way of maintaining flora biodiversity by requiring every new student to bring unique or rare plant seeds from their hometown. The Kiai and teacher at the school have progressive thoughts about the human’s relationship with God and nature. Human is God’s representative who is obliged to maintain the environment and natural elements including biodiversity. The students generally have adequate awareness and concern for the environment and sustainability which is largely influenced by the figure of the Kiai. The findings of this study imply that Islamic boarding school (pesantren) can play essential role in practicing and raising awareness of sustainable environmental management and biodiversity conservation.